Pendampingan Implementasi SPMI di Sekolah Model dan Sekolah Imbas SMA Kota Mataram 2019 - Sugeng Prayoga (Jurnal Paedagogy, 2020)
The objectives of assisting in the implementation of SPMI in model schools and the impact schools of Mataram City High Schools are: to (1) improve the quality of education in accordance with national education standards and create a culture of quality education in education units; (2) Increase the understanding of SPMI to supervisors, school principals, teachers, education personnel, parents / school committees and stakeholders in and outside the model school; (3) Improving school skills in implementing SPMI; (4) Strengthening the implementation of SPMI to supervisors, principals, teachers, other education personnel, parents / school committees and stakeholders in and outside the model school. The assistance of SPMI implementation in model schools and impact schools consists of several series of activities, namely; (1) Model school and school preparatory meetings, (2) In 1: Quality mapping assistance, (3) On 1: Assistance to the implementation of the SPMI cycle, (4) In 2: Quality planning assistance, (5) On 2: Continuing mentoring implementation of the SPMI cycle and internal audit, (6) On 3: Assistance for quality fulfillment and preparation of SPMI best practices, and (7) In 3: Dissemination of best practice results from the implementation of the SPMI cycle. The results of the SPMI implementation assistance activities include; (1) Model and impact schools can implement education quality assurance independently; (2) Model and impact schools can improve quality according to national education standards; (3) There is an increase in quality culture in model and impact schools; (4) Improved school management consisting of document 1, school self-evaluation, RKS, infrastructure, finance and vision and mission of the school; (5) the establishment of educators and education staff as well as the learning process; (6) Model schools can be modeled as SNP-based schools through the implementation of education quality assurance independently and implementing the pattern of application of education quality assurance to other schools until all schools are skilled in implementing education quality assurance independently.